Salmonellas in Danish pigs: a comparison of three isolation methods. - Skovgaard, N. (Cambridge University Press, 1985)
Caecal samples from 350 Danish bacon pigs were investigated for salmonella using three methods of isolation. (1) Direct inoculation of 1 g of faeces into 10 ml of Muller-Kaufmann medium (MK medium) with addition of 0.3% Teepol 610 and subculture on Brilliant Green lactose sucrose phenol-red agar (BLSF agar) with 0.3% Teepol 610. (2) Pre-enrichment of 5 g of faeces into buffered peptone water with addition of 1% Teepol 610 followed by enrichment of 1 ml in 10 ml MK medium with 1% Teepol 610 and subculture on BLSF agar with 0.3% Teepol. (3) Incubation of 0.1 ml of the pre-enrichment (2) into 10 ml Rappaport-Vassiliadis medium (RV 10 medium) incubated at 43 degrees C, subculture on BLSF agar. The MK media with and without pre-enrichment yielded higher findings than the RV 10 media. In total, 28 (8%) of the pigs were found positive, representing 11 (7.4%) of a total of 142 herds investigated. Lymph glands were collected at a later date from six of the positive herds. Five of the herds were found positive. The number of salmonellas in the glands was low, probably less than ten per gram.